BIOLOGICAL SEED TREATMENT FOR CONTROLLING ANTHRACNOSE DISEASE OF HOT PEPPER - G.A.K. Sutariati; Widodo .; Sudarsono .; S. Ilyas (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2014)
Three rhizobacteria (Bacillus polymixa  BG25,  Pseudomonas fluorescens  PG01 and Serratia liquefaciens SG01) which inhibited the conidia germination of Colletotrichum capsici  and produced the phytohormone indoleacetic acid (IAA) were selected and evaluated as biocontrol agents for controlling Colletotrichum capsici, the causal agent of hot pepper anthracnose and for improving the growth, yield and seed quality of hot pepper in glasshouse and field conditions. Two cultivars of hot pepper, cv. Lokal Brebes and cv. Tit Super were also used in this experiment. The result of the experiment showed that seed treatments with P. fluorescens PG01 either alone or in combination with B. polymixa BG25 increase yields and seed quality under glasshouse and field conditions. However, the most effective treatment was the combination of both agents. Moreover, biological seed  treatment with P. fluorescens PG01 either alone or in combination with B. polymixa BG25 led to induction of resistance against C. capsici, as a result of increase in peroxidase activity and biosynthesis of phytoalexins that have been considered as resistance mechanisms against plant diseases.